Chewing lice of the Brueelia-complex (Phthiraptera: Ischnocera) parasitic on members of the Campephagidae (Aves: Passeriformes), with description of a new subgenus and 14 new species - Gustafsson, Daniel R.; Bush, Sarah E. (Zootaxa, 2022)
Fourteen new species of chewing lice in the Brueelia-complex are described, from hosts in the Campephagidae. In addition, Malardifax a new subgenus of Guimaraesiella Eichler, 1949 is described for the species occurring on minivets (Campephagidae: Pericrocotus). The new species and their hosts are: Guimaraesiella (Guimaraesiella) nouankaoensis n. sp. from Coracina caledonica seiuncta Mayr & Ripley, 1941 and C. caledonica thilenii (Neumann, 1915); Guimaraesiella (Guimaraesiella) sphagmotica n. sp. from Coracina caeruleogrisea strenua (Schlegel, 1871) and C. caeruleogrisea adamsoni Mayr & Rand, 1936; Indoceoplanetes (Capnodella) kamphaengphetensis n. sp. from Lalage melaschistos avensis (Blyth, 1852); Indoceoplanetes (Capnodella) saucia n. sp. from Edolisoma montanum montanum (Meyer, 1874); Indoceoplanetes (Capnodella) subarcens n. sp. from Edolisoma melas melas (Lesson, 1828); Indoceoplanetes (Indoceoplanetes) cinitemnina n. sp. from Edolisoma melas melas (Lesson, 1828); Indoceoplanetes (Indoceoplanetes) ephippiformis n. sp. from Edolisoma montanum montanum (Meyer, 1874); Indoceoplanetes (Indoceoplanetes) fodincana n. sp. from Coracina papuensis oriomo Mayr & Rand, 1936, C. papuensis angustifrons (Salvadori, 1876), and C. papuensis elegans (Ramsay, 1881); Indoceoplanetes (Indoceoplanetes) incisoma n. sp. from Coracina macei siamensis (Baker, 1918) and C. macei rexpineti (Swinhoe, 1863); Indoceoplanetes (Indoceoplanetes) microgenitalis n. sp. from Coracina caeruleogrisea strenua (Schlegel, 1871); Indoceoplanetes (Indoceoplanetes) pterophora n. sp. from Coracina macei nipalensis (Hodgson, 1836); Indoceoplanetes (Indoceoplanetes) saburrata n. sp. from Coracina lineata ombriosa (Rothschild & Hartert, 1905); Indoceoplanetes (Indoceoplanetes) wandoensis n. sp. from Coracina novaehollandiae melanops (Latham, 1802); and Indoceoplanetes (Indoceoplanetes) zambica n. sp. from Coracina pectoralis (Jardine & Selby, 1828). Checklists and keys to the louse species of the Brueelia-complex parasitic on campephagid hosts are provided.